Acquired Localized Cutis Laxa due to Increased Elastin Turnover - Rie Harboe Nygaard; Scott Maynard; Peter Schjerling; Michael Kjaer; Klaus Qvortrup; Vilhelm A. Bohr; Lene J. Rasmussen; Gregor B.E. Jemec; Michael Heidenheim (Karger Publishers, 2016)
Cutis laxa is a rare disease characterized by abnormal skin wrinkling and laxity, due to decreased elastin synthesis or structural extracellular matrix defects. We have explored elastin metabolism in a case of adult onset cutis laxa localized to the upper body of a woman. For this purpose, we obtained skin biopsies from affected and unaffected skin areas of the patient and analyzed these with microscopy, polymerase chain reaction, western blotting and cell culture experiments. Skin from the affected area lacked elastin fibers in electron microscopy but had higher mRNA expression of elastin and total RNA. Levels of an apparent tropoelastin degradation product were higher in the affected area. Fibroblast cultures from the affected area were able to produce elastin and showed higher proliferation and survival after oxidative and UVB stress compared to fibroblasts from the unaffected area. In conclusion, we report a case of acquired localized cutis laxa with a lack of elastic fibers in the skin of the patient's upper body. The lack of elastic fibers in the affected skin was combined with increased mRNA expression and protein levels of elastin. These findings indicate that elastin synthesis was increased but did not lead to deposited elastic fibers in the tissue.